2017
DOI: 10.1111/an.383
|View full text |Cite
|
Sign up to set email alerts
|

Teaching from a Place of Hope in Indigenous Education

Abstract: Teaching from a place of hope, as explored in this session, emerges from continuity, persistence and relationships. These characteristics are needed today, just as they were needed yesterday.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The results of research in this field show a positive relationship between the construct of hope and various variables, such as self-efficacy ( Fathi and Derakhshan, 2019 ), academic performance ( Chahkandi et al, 2016 ; Mellati and Khademi, 2020 ), life satisfaction ( Csizer and Lukacs, 2010 ), academic success ( Tsuda and Nakata, 2013 ), interest and motivation to continue education ( Papi, 2018 ), intellectual conflict ( Rose et al, 2018 ), general wellbeing ( Greenier et al, 2021 ), and resilience ( Ong et al, 2006 ), and its negative relationship with academic stress ( Derakhshan et al, 2021 ), school violence ( Dewaele and MacIntyre, 2014 ), and academic procrastination and self-disability ( Dornyei, 2011 ). A study by Chew and Vanessa (2017) also showed that the overall expectation of 44% of the variance, according to Snyder’s theory of hope ( Snyder and Lopez, 2007 ), is an active process in which people choose goals and try to achieve them by designing different paths. This basis seems to be related to the strategies that people adopt to achieve their educational goals.…”
Section: Review Of Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…The results of research in this field show a positive relationship between the construct of hope and various variables, such as self-efficacy ( Fathi and Derakhshan, 2019 ), academic performance ( Chahkandi et al, 2016 ; Mellati and Khademi, 2020 ), life satisfaction ( Csizer and Lukacs, 2010 ), academic success ( Tsuda and Nakata, 2013 ), interest and motivation to continue education ( Papi, 2018 ), intellectual conflict ( Rose et al, 2018 ), general wellbeing ( Greenier et al, 2021 ), and resilience ( Ong et al, 2006 ), and its negative relationship with academic stress ( Derakhshan et al, 2021 ), school violence ( Dewaele and MacIntyre, 2014 ), and academic procrastination and self-disability ( Dornyei, 2011 ). A study by Chew and Vanessa (2017) also showed that the overall expectation of 44% of the variance, according to Snyder’s theory of hope ( Snyder and Lopez, 2007 ), is an active process in which people choose goals and try to achieve them by designing different paths. This basis seems to be related to the strategies that people adopt to achieve their educational goals.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Various studies ( Dale, 2003 ; Ong et al, 2006 ; Martin, 2014 ; Chen and Park, 2016 ; Chew and Vanessa, 2017 ; Gallagher and Lopez, 2018 ; Mellati et al, 2018 ) have shown that hope is associated with positive emotions, feelings of self-worth, academic performance, and motivation in language learners. The results of these studies showed that students who have a higher level of hope are at a high level in terms of the orientation of achievement and education goals ( Chen and Park, 2016 ).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The singularity of the “I” is here contrasted to alternative concepts of “we” characterized by holistic societies; holisticism is the perception that something cannot be grasped independent of its context, parts cannot be separated from the whole. Indigenous groups, while by no means homogenous culturally, perceive hope as a collective good, a dynamic, powerful, and imaginative force connecting well-being in the natural–spiritual domain (Chew and Anthony-Stevens 2017; Durie 2001; Stewart-Harawira 2005). Indigenous ontology perceives of the interconnectivity of all existence in a matrix—all as a manifestation of matter or spirit, energy or material in a never-ending transmutation that cannot be grasped in single assessment.…”
Section: The Diversity Of Hopementioning
confidence: 99%